Изнашивание гальванических покрытий на основе золота; Физическая мезомеханика; Т. 18, № 3 - Шугуров А. Р. Артур Рубинович; Панин А. В. Алексей Викторович; Лязгин А. О. Александр Олегович; Шестериков Е. В. Евгений Викторович (2015, 2015)
Заглавие с экрана